Empowerment at the Crossroads: Women's Educational Challenges in Karachi's Higher Education - Rahat, Aisha Bano; Nisa, Aziz Un; Siddiqua, Naila; Humma Mehmood; Abbassi , Rahama (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2024)
This study investigates the challenges faced by female students pursuing higher education in Karachi, Pakistan. It explores the barriers and difficulties that women experience in accessing and completing their higher education, as well as the factors that hinder women's education in society. The study utilized a descriptive; quantitative survey approach was used, questionnaire with multiple choices. Which was administered to 300 randomly selected female respondents from various departments of the University of Karachi and Federal Urdu University. The study also proposes guidelines to address these challenges and minimize their impact. The research findings reveal the perceptions and experiences of female students in higher education, emphasizing the need for gender equality, inclusive support systems, and diverse representation in academic leadership positions. The study's outcomes can enlighten policymakers, educational institutions, and stakeholders in enhancing female empowerment and educational opportunities in Karachi The findings of the study reveal the perceptions and experiences of female students in higher education, highlighting the need for gender equality, inclusive support systems, and diverse representation in leadership positions.